(untitled) (Mongolian Journal of Astronomy and Geophysics, 2024)
This paper presents the results of geomagnetic measurements conducted along 23 profiles in the 740-hectare Uvur Khooloi area, located 35 km northwest of the centre of Dashbalbar Sum, Dornod Province. The data were processed and combined with the geological map of the area for interpretation. In this study, anomalies associated with the lithosphere were extracted from the total geomagnetic field measurements on the Earth’s surface, and an anomaly distribution map was created for the area. The magnetic anomaly map for Uvur Khooloi revealed a linear structure approximately 120 meters wide, with a high amplitude and a positive magnetic anomaly in the northeastern part of the area. Furthermore, a 2-D magnetic susceptibility distribution model across the linear structure was developed to understand the subsurface characteristics of the structure. The geological map of the area indicated that faults extending from southwest to northeast explained the geometric features of the linear structure observed in the geomagnetic field measurements. The positive geomagnetic anomalies correspond spatially with unsorted volcanic rocks and conglomerate sediments cut by short, north-south trending faults.